2008
DOI: 10.1080/10494820802114242
|View full text |Cite
|
Sign up to set email alerts
|

Blending coherence and control in the construction of interactive educational narratives from digital resources

Abstract: Digital learning environments are generally composed of resources that cumulatively meet some specified educational objective, with each resource facilitating the acquisition of a subset of the concepts to be learned. In such contexts narrative has, for example, been used to support the understanding and navigation of a course or curriculum structure into which the resources have been pre-organised. Conversely, we focus on educational contexts where the unit of learning is concepts derived across the constitue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Journalists have found that readers are more likely to complete the entire interactive story when a narrative is used (Dick, 2014). Interactive narrative allows learners to explore, look at content from different viewpoints, and consider each piece as a part of the whole (Mulholland, Wolff, Zdrahal, & Collins, 2008). The narrative serves to frame experience, helping the learner process the information with less cognitive effort (Bruner, 1990).…”
Section: Narrativementioning
confidence: 99%
“…Journalists have found that readers are more likely to complete the entire interactive story when a narrative is used (Dick, 2014). Interactive narrative allows learners to explore, look at content from different viewpoints, and consider each piece as a part of the whole (Mulholland, Wolff, Zdrahal, & Collins, 2008). The narrative serves to frame experience, helping the learner process the information with less cognitive effort (Bruner, 1990).…”
Section: Narrativementioning
confidence: 99%
“…The terms learning objective, educational objective, and instructional objective are especially common as catch-all terms and used in generic ways. For example, some authors use learning objective to refer to more general objectives (Schamber & Mahoney, 2006;Mulholland, Wolff, Zdrahal, & Collins, 2008); Novakowski (2009) use the term educational objective in a similarly broad manner. d 'Ham, de Vries, Girault, and Marzin (2004) provide examples of how they define learning objectives, "Identify objects and phenomena and become familiar with them, Learn a fact or facts, Learn how to carry out a standard procedure" (p. 427), which suggest a structure similar to a Tyler-type objective (Tyler, 1971).…”
Section: Terminology Of Objectivesmentioning
confidence: 99%